2001
DOI: 10.1093/jn/131.10.2677
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Zinc Status Are Suboptimal in a Sample of Older New Zealand Women in a Community-Based Study

Abstract: The importance of selenium and zinc in the immune functioning of the aged is widely recognized. Seniors in New Zealand are at particularly high risk of low selenium status because of the low selenium soil environment. The zinc status of the New Zealand elderly has never been assessed. In this cross-sectional study, the biochemical selenium, zinc and lipid levels, physical functional capacity and dietary intakes of 103 randomly selected free-living New Zealand women (mean age +/- SD, 75 +/- 3 y) were assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 43 publications
3
49
2
2
Order By: Relevance
“…Estudios realizados en distintos países muestran que los adultos mayores constituyen un grupo que presenta una elevada prevalencia de defi ciencia de zinc, especialmente en los grupos más pobres, en aquellos que se encuentran institucionalizados u hospitalizados y en los países en vías de desarrollo [11][12][13][14][15][26][27][28] . Sin embargo, la información referente a la prevalencia de la defi ciencia de cobre es prácticamente inexistente.…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
See 1 more Smart Citation
“…Estudios realizados en distintos países muestran que los adultos mayores constituyen un grupo que presenta una elevada prevalencia de defi ciencia de zinc, especialmente en los grupos más pobres, en aquellos que se encuentran institucionalizados u hospitalizados y en los países en vías de desarrollo [11][12][13][14][15][26][27][28] . Sin embargo, la información referente a la prevalencia de la defi ciencia de cobre es prácticamente inexistente.…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
“…Diversos estudios nacionales 19,30,31 , regionales 13,15 , otros países en vías de desarrollo 27 e incluso de países desarrollados 26,28,32,33 han mostrado una ingesta inadecuada de zinc en los adultos mayores, acentuándose la reducción de la ingesta con la edad 5 . Por otra parte, una ingesta insufi ciente de cobre en este grupo etario ha sido demostrada en estudios nacionales 19,29 y algunos realizados en países desarrollados 32,34 .…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
“…Intake estimates from the 1997 National Nutrition Survey were only two-thirds the Australian recommended daily intake. More recent studies in younger New Zealand adults still indicate an insufficient Se intake for full expression of glutathione peroxidase (GPx) and do not confirm the earlier findings of 1996 [22].…”
Section: Protective Factors -Selenium and Zincmentioning
confidence: 81%
“…Therefore, the older the person the higher the blood Cd level is likely to be. It has also been suggested that, as populations age, their intake of Se and Zn decreases due to age-related changes in diet [22]. As prostate cancer risk increases with age, these changes in trace element exposure may further increase prostate cancer risk.…”
Section: Prostate Cancer and Environmental Trace Elementsmentioning
confidence: 99%
See 1 more Smart Citation